INFLUENCE OF POLITICAL CONNECTIONS AND SOCIAL-ENVIRONMENTAL EVIDENCE ON THE COST OF CAPITAL - Koprowski, Sirlene; Krein, Viviane; Barichello, Rodrigo; Mazzioni, Sady; Baú Dal Magro, Cristian (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
The objective of the study is to verify the influence of political connections and socioenvironmental disclosure on the cost of capital of companies. The survey sample consisted of 275 companies listed in B3. The findings reveal that: a) the level of social and environmental disclosure positively influences the cost of capital of companies, especially the cost of third-party capital; b) political connections, in isolation, negatively influence the cost of capital and positively the cost of capital of third parties; c) and moderate negatively, the relationship between socioenvironmental disclosure and cost of equity. Therefore, political connections reduce shareholder returns, create constraints on credit institutions that require a higher cost of capital and become harmful to companies by curbing the effect of socio-environmental practices on the return of equity.